Preparation of magnetic mesoporous silica nanoparticles as a multifunctional platform for potential drug delivery and hyperthermia. Issue 1 (1st December 2016) - Yu, Xia; Zhu, Yufang
Abstract: We report the preparation of magnetic mesoporous silica (MMS) nanoparticles with the potential multifunctionality of drug delivery and magnetic hyperthermia. Carbon-encapsulated magnetic colloidal nanoparticles (MCN@C) were used to coat mesoporous silica shells for the formation of the core-shell structured MMS nanoparticles (MCN@C/mSiO2 ), and the rattle-type structured MMS nanoparticles (MCN/mSiO2 ) were obtained after the removal of the carbon layers from MCN@C/mSiO2 nanoparticles. The morphology, structure, magnetic hyperthermia ability, drug release behavior, in vitro cytotoxicity and cellular uptake of MMS nanoparticles were investigated. The results revealed that the MCN@C/mSiO2 and MCN/mSiO2 nanoparticles had spherical morphology and average particle sizes of 390 and 320 nm, respectively. The MCN@C/mSiO2 nanoparticles exhibited higher magnetic hyperthermia ability compared to the MCN/mSiO2 nanoparticles, but the MCN/mSiO2 nanoparticles had higher drug loading capacity. Both MCN@C/mSiO2 and MCN/mSiO2 nanoparticles had similar drug release behavior with pH-controlled release and temperature-accelerated release. Furthermore, the MCN@C/mSiO2 and MCN/mSiO2 nanoparticles showed low cytotoxicity and could be internalized into HeLa cells. Therefore, the MCN@C/mSiO2 and MCN/mSiO2 nanoparticles would be promising for the combination of drug delivery and magnetic hyperthermia treatment in cancer therapy. Abstract :